Pharmacological Targeting of the Actin Cytoskeleton to Drive Endocrinogenesis. (June 2020) - Siehler, Johanna; Blöchinger, Anna Karolina; Lickert, Heiko
Abstract : In vitro generation of insulin-secreting beta cells from human pluripotent stem cells (hPSCs) opens new avenues for treating and modeling diabetes. Hogrebe and colleagues established a new 2D differentiation protocol where they targeted the cytoskeleton pharmacologically for controlled endocrine induction and generation of hPSC-derived beta cells with improved function.